Sociální ekonomika a nestátní neziskové organizace - Halásková, Renáta (Univerzita Pardubice, 2008)
The article concenrns the definition of the concept of the non-profitable sector and social economics and their comparation. The attention is mainly paid to the role of non-profitable organisations in non-profitable sector and in the area of social economics.
Keywords: social economics; non-profitable sector; non-profitable organisation; non-profitable organisation providing social service